2021
DOI: 10.21203/rs.3.rs-309470/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of temperature on the residual shear strength of fine grained soil

Abstract: The impact of low-range temperature variation on the residual shear strength parameters has been investigated. For this purpose, a standard ring shear apparatus has been subjected to low-cost modifications and equipped with thermoelectric temperature control system constructed in-house. This allowed to conduct a series of tests for clay samples at temperatures of 5°C and 20°C, which is a typical range of variation for thermo-active structures during heat extraction. In order to distinguish the impact of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Changing the temperature during shearing without removing the loading arms from the top cap prohibits the specimen to experience the full thermally-induced volume changes and potentially disrupts the results . On the other hand, the study by [4] concluded that there is no significant effect of temperature on residual shear strength of soil. In [4], the specimen was cooled to 5°C at the beginning of the consolidation stage and was sheared after reaching desired normal effective stress.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Changing the temperature during shearing without removing the loading arms from the top cap prohibits the specimen to experience the full thermally-induced volume changes and potentially disrupts the results . On the other hand, the study by [4] concluded that there is no significant effect of temperature on residual shear strength of soil. In [4], the specimen was cooled to 5°C at the beginning of the consolidation stage and was sheared after reaching desired normal effective stress.…”
mentioning
confidence: 97%
“…In [4], the specimen was cooled to 5°C at the beginning of the consolidation stage and was sheared after reaching desired normal effective stress. The main difference between these two described procedures is that [3] changed the temperature as the specimen was sheared, while [4] changed the temperature of the specimen prior to the consolidation stage.…”
mentioning
confidence: 99%